Influence of the amount of food resources in the foraging behavior of Nasutitermes corniger (Motschulsky) (Bioscience Journal, 2020)
Food scarcity or abundance are factors regulating termites’ foraging behavior in general. The aim of the present study is to evaluate the influence of four amounts of Eucalyptus grandis on foraging behavior events shown by worker and soldier of Nasutitermes corniger during laboratory tests. The tests were carried out with adult and active N. corniger colonies found in nests collected in the field, which were stored in glass cubes connected to the test arenas. Four different amounts of wood blocks were used in the tests and each amount concerned a treatment and defined a different experimental group: 1, 2, 3 and 4 blocks/arenas, with 5 repetitions. Each test lasted 60 minutes and consisted in observing, or not, the occurrence of behavioral events shown by foragers when they had contact with the treatment. The duration of each event was recorded, whenever it was observed. The number of recruited foragers and the number of workers consuming the blocks were recorded at the end of each test applied to each treatment. Nasutitermes corniger presented the three behavioral events in all treatments; however, there was not significant difference between treatments in the occurrence of the two first events, in the time taken from test start to the occurrence of a new event, in the number of recruited termites and in the number of gnawing workers. Only workers’ mass recruiting was influenced by the amount of wood available. The occurrence of this event was significantly higher in treatments with greater amounts of wood. Thus, N. corniger adjusts its mass recruitment behavior in response to available food amount, which should be considered when developing baiting system for its control.